2011
DOI: 10.5194/esdd-2-493-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downscaling climate change scenarios for apple pest and disease modeling in Switzerland

Abstract: As a consequence of current and projected climate change in temperate regions of Europe, agricultural pests and diseases are expected to occur more frequently and possibly to extend to previously not affected regions. Given their economic and ecological relevance, detailed forecasting tools for various pests and diseases have been developed, which model their phenology depending on actual weather conditions and suggest management decisions on that basis. Assessing the future risk of pest-related damages requir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Despite the large associated uncertainties regarding precipitation projections, the results here give rise to further discussion and research. Changes in wet-day frequency and intensity could help adjusting calibrated weather generator parameters to mimic future weather with the appropriate temporal sequence (Jones et al, 2011;Hirschi et al, 2012). Likewise, results on precipitation-type shifts could be used to modify conditional resampling techniques for a future climate (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large associated uncertainties regarding precipitation projections, the results here give rise to further discussion and research. Changes in wet-day frequency and intensity could help adjusting calibrated weather generator parameters to mimic future weather with the appropriate temporal sequence (Jones et al, 2011;Hirschi et al, 2012). Likewise, results on precipitation-type shifts could be used to modify conditional resampling techniques for a future climate (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 With the projected temperature increase, agricultural pest infestations and diseases are expected to occur more frequently and possibly expand to previously unaffected regions. 7 Predictions about the future biogeographical ranges of species are usually developed using models based on the climate variables that best describe current equilibrium distributions. Future distributions are then simulated under selected climate change scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Warmer temperatures may induce migration of crop enemies toward the poles (Wolfe et al 2008), increase the abundance of enemies (Hakala et al 2011), and increase the number of generations of pests during the growing season (Luedeling et al 2011;Hirschi et al 2012;Juszczak et al 2013), leading to a subsequent increase in pesticide use. Warmer temperatures may also advance the growth period, along with application dates (Hirschi et al 2012), and accelerate biodegradation of pesticides (Bloomfield et al 2006;Shymko et al 2011;Balbus et al 2013;Steffens et al 2013), possibly reducing exported loads per application but also possibly leading to more applications (Bloomfield et al 2006). Increase in CO 2 may particularly benefit C 3 plants, either crops or weeds (Stratonovitch et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently in Qu ebec, there are up to 2 generations of codling moth per year. Some studies have suggested that the number of generations of codling moth per year could further increase in the future (Luedeling et al 2011;Hirschi et al 2012;Juszczak et al 2013). Plum curculio is one of the most important pests for pome and stone fruits in eastern North America (Chouinard 2014b;Hock et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation